Maternal Glucose and LDL-Cholesterol Levels Are Related to Placental Leptin Gene Methylation, and, Together With Nutritional Factors, Largely Explain a Higher Methylation Level Among Ethnic South Asians - Sletner, Line; Moen, Aina E. F.; Yajnik, Chittaranjan S.; Lekanova, Nadezhda; Sommer, Christine; Birkeland, Kåre I.; Jenum, Anne K.; Böttcher, Yvonne (Frontiers in Endocrinology, 2021)
Background: Leptin, mainly secreted by fat cells, plays a core role in the regulation of appetite and body weight, and has been proposed as a mediator of metabolic programming. During pregnancy leptin is also secreted by the placenta, as well as being a key regulatory cytokine for the development, homeostatic regulation and nutrient transport within the placenta. South Asians have a high burden of type 2 diabetes, partly attributed to a “thin-fat-phenotype”. Objective: Our aim was to investigate how maternal ethnicity, adiposity and glucose- and lipid/cholesterol levels in pregnancy are related to placental leptin gene (LEP) DNA methylation. Methods: We performed DNA methylation analyses of 13 placental LEP CpG sites in 40 ethnic Europeans and 40 ethnic South Asians participating in the STORK-Groruddalen cohort. Results: South Asian ethnicity and gestational diabetes (GDM) were associated with higher placental LEP methylation. The largest ethnic difference was found for CpG11 (5.8% (95% CI: 2.4, 9.2), p<0.001), and the strongest associations with GDM was seen for CpG5 (5.2% (1.4, 9.0), p=0.008). Higher maternal LDL-cholesterol was associated with lower placental LEP methylation, in particular for CpG11 (-3.6% (-5.5, -1.4) per one mmol/L increase in LDL, p<0.001). After adjustments, including for nutritional factors involved in the one-carbon-metabolism cycle (vitamin D, B12 and folate levels), ethnic differences in placental LEP methylation were strongly attenuated, while associations with glucose and LDL-cholesterol persisted. Conclusions: Maternal glucose and lipid metabolism is related to placental LEP methylation, whilst metabolic and nutritional factors largely explain a higher methylation level among ethnic South Asians.